Motherisk Update: Pharmacologic treatment of nausea and vomiting during pregnancy - Mazzotta, Paolo (1998)
QUESTION: Some of my pregnant patients have trouble functioning because of morning sickness. In particular, they are afraid to take medications. They end up losing weight, quitting work, and dropping out of other activities. What can I do to allay their fears? ANSWER: Women often benefit from knowing that they are not alone in having this problem, that morning sickness typically does not harm a fetus, and that safe therapies are available. Psychological and medical support is very important. Other causes of nausea and vomiting must always be ruled out. The Motherisk Program has a clinic and hot-line line for patients with severe morning sickness.